Bioactive potential of Mytilus galloprovincialis hydrolysates: effect of hydrolysis conditions and sample processing - Moura, Maria Eduarda Nogueira (2023)
This internship allowed integration in the ValorMar project, aimed at improving aquaculture industries while also providing health benefits to humans. Aquaculture generates great amounts of waste and by-products, which constitutes an economic, health and environmental problem. These by-products are known to possess nutritional and bioactive potential, worthy of exploration for the manufacture of novel functional foods, that can exert specific beneficial effects on human health and wellbeing. Therefore, the goal of the present work was to explore the bioactive potential of the Mediterranean mussel (Mytilus galloprovincialis), a common European aquaculture shellfish product, that generates high amounts of waste, through enzymatic hydrolysis, to extract potentially bioactive compounds that can later be applied in the creation of new functional foods. Mussel meat homogenates were subjected to hydrolysis with Alcalase® and Protamex®, at pH 7.5, temperature of 60 °C, with different enzyme concentrations (0, 1, 2 and 3%), substrate amounts (25 and 50 g) and duration (1 and 2h). Resultant hydrolysates were further processed through lyophilization or Amicon® ultrafiltration. Pre-thermal-treatment, hydrolysis and hydrolysates processing conditions were evaluated to understand which would lead to the production of bioactive peptides. Hydrolysates were tested for their antioxidant ability, through 2,2-diphenyl-1- picrylhydrazyl (DPPH) radical scavenging method, antimicrobial activity, by disk and well diffusion techniques, and for antihypertensive ability by their capacity in inhibiting angiotensin-converting enzyme (iACE). Produced hydrolysates revealed that multiple enzyme hydrolysis produces higher bioactive potential. DPPH scavenging ability increased with substrate and revealed lower activity with the >3 kDa fraction, unlike iACE potential, which increased with the ultrafiltered fraction. In general, boiled mussel hydrolysates showed high antihypertensive potential. However, no antimicrobial effect was observed from samples obtained in the tested conditions. Further studies should be done, widening hydrolysis and purification conditions, testing for different bioactive potential, to gather more knowledge on this species potential as a source of bioactive compounds. Further assays are required to assess hydrolysates stability in food matrices and during digestion, and their effect on target sites.